2011
DOI: 10.1158/1078-0432.ccr-10-0752
|View full text |Cite
|
Sign up to set email alerts
|

p27: A Barometer of Signaling Deregulation and Potential Predictor of Response to Targeted Therapies

Abstract: Phosphorylation of the cyclin-dependent kinase inhibitor p27 by upstream mitogenic signaling pathways regulates its stability, localization and biological function. In human cancers, loss of the antiproliferative action of p27 can arise through reduced protein levels and/or cytoplasmic mislocalization leading to increased cell proliferation and/or cell migration, respectively. Reduced p27 expression levels and p27 mislocalization have potential prognostic and therapeutic implications in various types of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 90 publications
12
159
1
9
Order By: Relevance
“…In the study of ES cells, SSEA-3 + cells reportedly showed a faster cell cycle (24), and we further detected the decreased expression of cyclin-dependent kinase inhibitors p21 and p27 in SSEA-3 + cells. p27 is not only a cell cycle inhibitory factor of G1/S transition, but also a differentiation-promoting factor (27), and decreased expression of p27 in SSEA-3 + population has been reported in teratocarcinoma (28). p21 negatively regulates not only G1/S transition, but also G2/M transition (29), and its relation to SSEA-3 expression has not been reported.…”
Section: Discussionmentioning
confidence: 97%
“…In the study of ES cells, SSEA-3 + cells reportedly showed a faster cell cycle (24), and we further detected the decreased expression of cyclin-dependent kinase inhibitors p21 and p27 in SSEA-3 + cells. p27 is not only a cell cycle inhibitory factor of G1/S transition, but also a differentiation-promoting factor (27), and decreased expression of p27 in SSEA-3 + population has been reported in teratocarcinoma (28). p21 negatively regulates not only G1/S transition, but also G2/M transition (29), and its relation to SSEA-3 expression has not been reported.…”
Section: Discussionmentioning
confidence: 97%
“…c-Myc represses the transcription of key growth control and differentiation genes, including p21, p27, and growtharrest and DNA-damage proteins (23,24). In addition, p27 reportedly acts as a barometer for targeted therapies, because reduced p27 levels and p27 mislocalization have potential prognostic and therapeutic implications (25). However, under dysregulated conditions, as seen in cancer cells, the threshold for these checkpoints, such as DNA damage repair during cell cycle, is avoided because cell-cycle suppressors, such as the p21Cip1/p27 family of CDK inhibitors, are reduced (11,12,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic p27-dependent promotion of cell migration was later shown by others to be due to direct interaction with the Rho GTPase, RhoA, and inhibition of its interactions with guanine nucleotide exchange factors (GEFs), which promote RhoA activation (Besson et al , 2004 ). This regulatory mechanism has been shown to contribute to tumor invasion and progression (Larrea et al , 2009b ) and is also thought to mediate tumor metastasis (Wander et al , 2011 ). Recently, it was shown that phosphorylation of p27 on Thr198, in this case by the kinase RSK1, was also associated with cytoplasmic localization and RhoA-dependent promotion of cell migration (Larrea et al , 2009a ).…”
Section: Cip/kip Family Of Proteins and Cancermentioning
confidence: 99%